Modelling Sediment Yield from the Microwatersheds of Western Ghats - Nandakumar, V.; Rajendran, P.; Ajith Kumar, C.E.; Abdul hakkim, V.M (Journal of Soil and Water Conservation, 2022)
Prioritizing the microwatersheds of Western Ghats within Kerala based onthe sediment yield is essential considering the cost involved in implementing soil and water conservation measures. In order to prioritize the microwatersheds in the area, sediment yield modelling is attempted by measuring the sediment yield from selected typical microwatersheds in the Western Ghats as well as by characterizing the various geomorphic, physiographic and soil characteristics from these microwatersheds Multiple regression analysis was done to develop the sediment yield model. A computer based working model is also developed in visual basic.